Budaya Patriarki Pernikahan Usia Dini Di Daerah Dusun Kendal, Pasean Kabupaten Pamekasan - Riskianti, Siti Sofa; Fajariah , Susanti (Yayasan Pendidikan Internasional Bengkulu, 2024)
Patriarchal culture is still a tradition in society's social life. One of them is early marriage, which is still practiced by some people today. Even though times are increasingly modern and science and technology are developing rapidly. Some people's low level of awareness of the dangers posed is actually seen as something that can make their daughters free from the assumption of being old maids. Patriarchal culture is a culture that places men in a higher position than women. So women become victims of domestic violence and even become the backbone of the family. Kendal Hamlet, Pasean, Pamekasan Regency considers early marriage as a tradition. When their daughters reach puberty, even though they are underage, they are considered adults and can be married off. The practice of spells is a shortcut to prevent their daughters from rebelling when they are arranged for marriage and manipulating the age of marriage. So it is not surprising that divorce cases are increasing due to arranged marriages. It is very important to carry out this research to explain the impact of the patriarchal culture of early marriage, especially on women, based on facts in the field. Parental awareness is the main object so that their decisions do not become an obstacle to the future of children who are not ready to face the realities of life.